Analysis of the Influence of Temperature Field on the Dynamic Modulus of Rubber Asphalt Pavement - Wang, Guoqing; Wang, Xinqiang; Yan, Zhanyou; Qin, Lusheng; Gao, Zhanhua (Frontiers in Materials, 2020)
In this paper, AMPT is used to study the dynamic modulus of different types of rubber asphalt mixtures in the laboratory, based on the viscoelastic theory, in order to determine the actual dynamic modulus of different structural layers under the action of temperature field in the asphalt pavement. Based on the time-temperature equivalence principle and Sigmund model, the dynamic modulus main curve is established. The actual dynamic modulus of asphalt concrete at each pavement layer is calculated by referring to the test data of pavement temperature field in Shijiazhuang and Tangshan. The data show that the dynamic modulus of asphalt mixture is significantly affected by temperature and loading frequency. Due to the influence of temperature field, the dynamic modulus of concrete in different structural layers will change dynamically. Under the effect of temperature field in winter, the minimum value of actual dynamic modulus of pavement is 1~2 times of the design value. Under the action of temperature field in summer, the maximum dynamic modulus of pavement structure layer is 62~72% of the design value. This study not only provides the basis for dynamic modulus selection in asphalt pavement design, but also has certain reference value for improving the life of asphalt pavement.